Broadcasting systems and standards of satellite television transmission in Europe - Jakšić Branimir S.; Maksimović Vladimir D.; Todorović Jelena M.; Spalević Mile M.; Spalević Petar LJ. (Tehnika, 2018)
In this paper the characteristics of satellite television transmission in the region of Europe are considered. An overview of the development of satellite television is given through the characteristics: broadcasting systems - analog and digital (SDTV, HDTV, UHDTV), frequency band (C, Ku, Ka), broadcasting standards (DVB-S, DVB-S2), the availability of TV services in the form of Free-to-air (FTA) and PAY TV, as well as the availability of TV services to satellite positions. Also, data are provided relating to satellite TV transmission providers. The collected data are presented by table and graphics for the period from 1996 to 2018. From the obtained results an analysis of the development of satellite television transmission was performed based on the characteristics of broadcasting.